El proceso defensivo del balonmano: una revisión sistemática (E-balonmano Com, Revista de Ciencias del Deporte, 2022)
The aim of this study was to identify the overview of original articles about the defensive phase of handball between the years 2000 and 2019, through a systematic review. Seven databases of scientific journals were consulted, based on pre-established criteria. Thirty-three articles were selected and revealed possible frontiers of knowledge about the teaching of handball. The results showed that the interest in this subject is recent, with the predominance of studies coming from Spanish universities, most of them being published in Spanish, followed by the English language. In general, there is a predominance of quantitative research when compared to assays, qualitative research or mixed methods. The contexts addressed in the studies investigated show the preference for the analysis of high performance teams in competitions such as World Championships and Olympic Games, especially men and adult teams.